Cloning, phylogenetic analysis, tissue expression profiling, and functional roles of NPC1L1 in chickens, quails, and ducks - Xin Shu; Ziwei Chen; Hui Wang; Bingjie Xu; Li Liu; Jilong Zhang; Xiaotong Zheng; Jianfei Chen (Poultry Science)
The Niemann-Pick C1-Like 1 (NPC1L1) protein, primarily expressed in the epithelial cells of the small intestine, is essential for cholesterol absorption from both dietary intake and biliary secretion. Despite this conserved function across mammals, the full-length coding sequence of NPC1L1 remains uncharacterized in key avian models including chicken (Gallus gallus), quail (Coturnix japonica), and duck (Anas platyrhynchos). In this study, we successfully cloned the full NPC1L1 mRNA sequence in chicken, quail, and duck, including the entire 5′ and 3′ untranslated regions, utilizing rapid amplification of cDNA ends methods. Phylogenetic analysis across 12 species, comprising four avian and eight representative mammalian species, revealed that the NPC1L1 sequences in the main poultry species exhibit a high degree of similarity. Despite the phylogenetic divergence of poultry NPC1L1 sequences from their mammalian counterparts, protein sequence alignment revealed that the cholesterol-sensing peptides of NPC1L1 are conserved across all species examined in this study. These findings imply that the NPC1L1 in poultry may also play a role in cholesterol transport. Analysis of tissue gene expression profiles in chickens, quails, and ducks indicated that NPC1L1 is predominantly expressed in the duodenum, jejunum, and liver. Additionally, experiments on medium-to-cell cholesterol transit in primary intestinal epithelial cells confirmed that chicken NPC1L1 is capable of efficiently transporting cholesterol into cells. Further experiments are required to elucidate the biological function of poultry NPC1L1. In summary, this study successfully cloned the full-length sequence of NPC1L1 from chickens, quails, and ducks, and conducted a comprehensive analysis of their evolutionary history and expression patterns. This research establishes a foundation for future investigations into the role of poultry NPC1L1 in cholesterol transport.